กระบวนการธุรกิจนำเข้าและการจัดจำหน่ายของภาพยนตร์อเมริกันในประเทศไทย - มนฑิรา ธาดาอำนวยชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research was aimed at investigating the business process of American movie importaion and distribution in Thailand. Results from depth interview demonstrated that all three distribution companies in Major group; i.e. Fox - Warner (Thailand) Co.,Ltd., UIP Co.,Ltd. and Columbia Tristar Buena Vista Films (Thailand) Co.,Ltd. had full power in selecting movies to exhibit in Thailand. The criterias for movie selection were different in each company. Information used for importation business process were content of movie itself. People involved in decision process were the headquarter in United States, regional offices (different for each company) and branch offices. In the part of branch offices, the brainstorming of General Manager, Sale Manager and Marketing Manager were held for decision making. An analysis of distribution process showed that all 3 companies didn t choose the channel of distribution process as the cinema business in Thailand is oligopoly which there are not many proprietors and the chance of new proprietor to enter the business was low. Thus, selecting relied on deal for each type of distribution. Besides, Theatre in Bangkok would exhibit all American movies while upcountry channels would select movies by considering the grade of movies and number of movie exhibiting and going to exhibit.